1997
DOI: 10.1103/physrevb.55.r14737
|View full text |Cite
|
Sign up to set email alerts
|

Vortex melting in polycrystallineYBa2Cu3et al.

Abstract: Line-shape analysis of 17 O NMR spectra is used to probe vortex melting and dynamics in aligned powders of YBa 2 O 3 O 7 . Vortex transitions are identified by comparing their dynamics with the NMR time scale. Lineshape changes indicate a well-defined melting transition at a temperature, T m . Below T m there is a coexistence regime of solid and liquid vortices with a lower bound, T g , which marks complete vortex freezing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
28
0
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 13 publications
5
28
0
1
Order By: Relevance
“…At T =5 K, the Redfield pattern indicates the vortex lattice. The similar, but narrow, coexistence region was first reported for YBa 2 Cu 3 O 7 [25,26]. The detailed measurement of vortex phase is in progress for our Tl2201 sample.…”
Section: Figure 5(a) Showsmentioning
confidence: 55%
“…At T =5 K, the Redfield pattern indicates the vortex lattice. The similar, but narrow, coexistence region was first reported for YBa 2 Cu 3 O 7 [25,26]. The detailed measurement of vortex phase is in progress for our Tl2201 sample.…”
Section: Figure 5(a) Showsmentioning
confidence: 55%
“…Above 77 and 60K respectively, we found δB = 0 within error bars (±4 G). For optimally doped samples and applied fields of a few Tesla, it has been shown that the vortices are in a liquid state in our range of temperatures below T c [13] [14]. Each vortex is then moving much faster than the NMR timescale, which averages out both the broadening and the screening effects, leading to δB = 0.…”
mentioning
confidence: 83%
“…It occurs at T m /T c = 0.61 in H = 11.6 T, and indicates that there is a substantial temperature range below T c where fluctuating vortices are in a liquid-like phase. We can compare this with YBa 2 Cu 3 O 7−y (YBCO) 48 50 that a confluence of weak thermal fluctuations and a very broad distribution of pinning forces gives rise to an irreversibility field significantly less than the upper critical field in crystals of Ba(Fe 0.9 Co 0.1 ) 2 As 2 . Generally the NMR spectrum is sensitive to field fluctuations on time scales slower than the Larmor precession period which is tens of nanoseconds in our case.…”
mentioning
confidence: 88%